Non-Invasive Estimation of Cardiac Index in Healthy Volunteers. Issue 3 (May 2018) - Eyeington, C. T.; Ancona, P.; Cioccari, L.; Luethi, N.; Glassford, N. J.; Eastwood, G. M.; Proimos, H. K.; Franceschi, F.; Chan, M. J.; Jones, D.; Bellomo, R.
The primary objective was to non-invasively measure the cardiac index (CI) and associated haemodynamic parameters of healthy volunteers and their changes with age. This was a single centre, prospective, observational study of healthy volunteers aged between 20 and 59 years, using the ClearSight™ (Edwards Life Sciences, Irvine, CA, USA) device. We recorded 514 observations in 97 participants. The mean CI was 3.5 l/min/m 2 (95% confidence interval [95% CI] 3.4 to 3.7 l/min/m 2 ). The mean stroke volume index (SVI) was 47 ml/m 2 (95% CI 45 to 49 ml/m 2 ) and the mean systemic vascular resistance index was 2, 242 dyne·s/cm 5 /m 2 (95% CI 2, 124 to 2, 365 dyne·s/cm 5 /m 2 ). There was an inverse linear relationship between increasing age and CI (P <0.0001), which decreased by 0.044 l/min/m 2 (95% CI −0.032 to −0.056 l/min/m 2 ) per year. This change was mostly due to a decrease in SVI of 0.45 ml/m 2 (95% CI 0.32 to 0.57 ml/m 2 ) per year (P <0.0001). The mean CI of young healthy humans is approximately 3.5 l/min/m 2 and declines by approximately 40 ml/min/m 2 per year, mostly due to a decline in stroke volume (SV). These findings have significant implications regarding the clinical interpretation of haemodynamic parameters and the application of these results to individual patients.